Modeling and Optimization of Tensile Strength of Arrowroot Bioplastic Using Response Surface Method. Issue 1 (June 2020) - Hendrawan, Y; Putranto, A W; Fauziah, T R; Argo, B D
Abstract: Biodegradable plastic or bioplastics made from starch or plants is one way to reduce plastic waste that is not environmentally friendly. Optimization of mechanical characteristics in bioplastics needs to be done, one of which are tensile strength and elongation. The purpose of this study is to find the best glycerol and chitosan compositions that produce the most optimal tensile strength and elongation of Arrowroot ( Maranta arundinacea L) bioplastic. The modeling and optimization method uses response surface method (RSM) with a central composite design (CCD). In the CCD, the glycerol composition was 2.4%, 3.9%, and 5.3% (1.5 g, 2.5 g, and 3.5 g of a solution of 62.5 mL, 64.5 mL, and 66.5 mL, respectively), while the composition of chitosan was 1.6%, 3.1%, and 4.5% (1 g, 2 g, and 3 g of a total solution of 62.5 mL, 64.5 mL, and 66.5 mL, respectively) with a total of 13 experimental designs on the CCD. The model results suggested by RSM-CCD are quadratic models. In the optimization results, the optimal solution is the addition of 2.554 g of glycerol and the addition of 2.068 g of chitosan which produces tensile strength of 96.219 MPa and elongation of 11.78% with a desirability value of 0.902. Validation results using three repetitions produce an average tensile strength of 95.82±0.65 MPa and elongation of 11.46±0.52. Under these condition, the error rate value both of responses are still below 5%, so that the model optimization can be accepted. The duration of bioplastic degradation (more than 75%) produced from the optimum value is 12 days.